Evidence-informed health policies in Eastern Mediterranean countries - Dimassi, Hani (2014)
The objective of this paper is to conduct comparative analysis about the views and practices of policy makers and researchers on the use of health systems evidence in policy making in selected Eastern Mediterranean countries. We analysed data from two self-reported surveys, one targeted at policy makers and the other at researchers. Results show a wide gap between policy makers and researchers when comparing perceptions on factors influencing the policy-making process and use of evidence in health policy making. Findings highlight specific areas for undertaking knowledge translation activities and implementing interventions to narrow the gap between policy makers and researchers.